Mental Map and Model Driven Development - von Pilgrim, Jens (Electronic Communications of the EASST, 2007)
In the case of a model driven development (MDD) approach, source models are transformed into destination models during the development process. This leads to a transformation chain, that is, a sequence of models connected via transformations. While so far usually only the domain models were transformed, we introduce an algorithm here to also transform the notation models, in order to create a diagram based on the layout of a predecessor diagram. We illustrate the algorithm on several examples which are visualized by a full-featured editor displaying 2D diagrams on layers in a 3D space.